Fostering a literacy culture in schools: the Role of teachers and families in encouraging interest in reading - Maulidya, Ruri (Maliki Interdisciplinary Journal, 2024)
Fostering a culture of literacy in schools is a crucial task in modern education. In this context, the role of teachers and families is very important in encouraging students’ interest in reading. Teachers have a responsibility to create an environment that supports literacy, such as providing interesting and relevant books, integrating reading into the curriculum, and teaching effective reading skills. Meanwhile, families play an important role in supporting students’ interest in reading at home, such as reading together, initiating discussions about books, and showing examples of positive reading behavior. These two roles complement each other, with the teacher providing the structure and skills, while the family provides the motivation and broader context. With collaboration between teachers and families, schools can create a strong literacy culture, which not only increases students’ interest in reading but also prepares them to become active and critical readers in the future.